Peninjauan Kembali terhadap Putusan Praperadilan: Analisis Kritis Kewenangan dan Pengaruhnya - Simamora, Sahat; Pakpahan, Zainal Abidin; Toni, Toni (SIGn Jurnal Hukum, 2024)
This study aims to analyze the legal authority related to filing for Judicial Review against Pretrial Rulings and its implications for the enforcement of justice in Indonesia. The study employs a normative legal research method with a statute approach. The collected legal materials are then analyzed qualitatively to describe the issues and address the research objectives. The research findings indicate that the authority to file for Judicial Review against Pretrial Rulings is a complex legal issue. Although Law Number 8 of 1981 does not explicitly provide for it, there are legal grounds that allow for such Judicial Review to be pursued. Suspects, Legal Advisor, and Prosecutors are the legal subjects authorized to file for Judicial Review. However, implementing Judicial Review against Pretrial Rulings still faces several challenges, particularly concerning public understanding and accessibility to the justice system. The Decision of Judicial Review on Pretrial Rulings has broad implications, not only affecting the fate of the individuals involved in the case but also contributing significantly to the protection of human rights, legal certainty, and improving the quality of law enforcement in Indonesia. The Supreme Court has a crucial role in providing clear and comprehensive guidelines regarding the technical implementation of Judicial Review against Pretrial Rulings, whether through the issuance of jurisprudence, a Circular of the Supreme Court, or reform of criminal procedural law. Reforming the procedure for filing for Judicial Review, which includes simplifying the procedure, intensifying public awareness campaigns, and optimizing the role of legal aid institutions, becomes crucial in enhancing access to justice and the protection of human rights.